Oneiric Film Sound and Human Brain - Milicevic, Mladen (European Scientific Journal, ESJ, 2016)
The focus of this paper is to connect an area of film studies (related to film sound) and recent findings in neuroscience. Since 1929 and Alfred Hitchcockâ€™s â€œBlackmailâ€ subjective film sound has been introduced and after that significantly â€œtweakedâ€ and redefined. However, it is quite interesting to observe that even though the filmmakers â€œintuitivelyâ€ arrived at the sort of â€œformulaâ€ for creating the oneiric sound experience, there is actually neuroscientific evidence that supports this â€œformulaâ€.